Immediate effect of instrumentation on the subgingival microflora in deep inflamed pockets under strict plaque control - G. E. Rhemrev (Blackwell Synergy, 2006)
Objective: To investigate (1) reduction in the number of microorganisms obtained directly after subgingival instrumentation, (2) rate of bacterial re-colonization during 2 weeks, under supragingival plaque-free conditions. Materials and Methods: Effects of subgingival instrumentation were measured at one deep pocket in 22 patients (11 smokers and 11 non-smokers). Immediately after initial therapy, experimental sites, under strict plaque control, were instrumented subgingivally. Microbiological evaluation was performed at pre-instrumentation, immediate post-instrumentation and 1 and 2 weeks post-instrumentation. Results: Mean total anaerobic clolony forming units (CFUs) dropped from 3.9 106 before to 0.09 106 immediately following instrumentation. Significant reductions were found for Tannerella forsythia, Micromonas micros, Fusobacterium nucleatum and spirochetes. Significant reductions were not observed for Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia and Campylobacter rectus. Except for spirochetes, no reduction in prevalence of specific periodontal bacteria was found immediately after instrumentation. During follow-up, mean total CFU tended to increase. Prevalence of periodontal bacteria further reduced. No effect of smoking was found. Conclusion: Results indicate that subgingival mechanical cleaning in itself, has a limited effect, in actually removing bacteria. The subsequent reduction in prevalence of specific periodontal bacteria shows that it is apparently difficult for these species to survive in treated pockets.